Carotid endarterectomy: The need for In vivo optical spectroscopy in the decision-making on intraoperative shunt usage – A technical note - Balaji, Arun; Rajagopal, Niranjana; Yamada, Yasuhiro; Teranishi, Takao; Kawase, Tsukasa; Kato, Yoko (Asian Journal of Neurosurgery, 2019)
Background: Carotid endarterectomy (CEA) is the surgical excision of the atherosclerotic plaque in patients with severe carotid artery stenosis. It is a common surgical technique required by neurosurgeons that should be mastered. In this article, we provide an outline of the technique and multimodality adjuncts involved in performing an effective CEA with a better surgical outcome. Materials and Methods: We have operated a total of 14 patients in our institute from 2015 to 2018. The male to female ratio is 13:1. Four (28.5%) patients were symptomatic and 10 (71.5%) were asymptomatic; with an average percentage of carotid stenosis being 81.2% in symptomatic and 76.6% in asymptomatic patients. Two patients have undergone bilateral CEA. Intraoperative monitoring was done with continuous in vivo optical spectroscopy (INVOS). Furui's double balloon shunt system was used to maintain blood flow from common carotid artery to the internal carotid artery, thus preventing cerebral ischemia in selected cases with significantly lateralized cerebral oximetry (CO) recordings. Results: Of the 14 patients with 16 CEA procedures, continuous INVOS monitoring was used in 12 CEA procedures. Of the 12 cases, only 5 (41.6%) needed a shunt. Furui's shunt was not used in 7 (58.3%) CEA procedures, where there were no changes in the intraoperative CO and these patients had an uneventful postoperative period. INVOS monitoring not only reduced the use of routine intraoperative shunt but also reduced the total surgical time and thus aided in preventing neurological complications. Conclusion: CEA should be strongly considered for symptomatic patients with >70% of carotid stenosis and in patients with 50%–69% stenosis if no other etiological basis for the ischemic symptoms can be identified. Continuous INVOS monitoring is mandatory for the decision of the use of intraoperative shunt, which reduces the perioperative morbidity and mortality significantly.
Keywords: Dual-image videoangiography; endarterectomy; in vivo optical spectroscopy; intraoperative shunt